A new MMIC sampling phase detector design for space applications. - Desgrez, S.
A new sampling phase detector monolithic microwave integrated circuit (MMIC) using a standard 0.18-μm GaAs technology has been designed and tested. The authors emphasize that commutation time has to be taken into account rather than pulse duration, as done in previous presented works. Thus, the new SPD design concept eases command-signal generation. It also solves the tradeoff between phase detection and RF signal input-to-output isolation through the use of a double sampler topology and a proper command-signal generation. It has been designed taking care of space level specifications and environment. Phase detection level above 2 Vpp and operating frequencies up to 20 GHz have been measured, although higher frequency operation can be expected.
Keywords: 0.18 micron; 20 GHz; GaAs; MMIC sampling phase detector; SPD design; Command-signal generation; Commutation time; Double sampler; Phase detection; Space applications; Space level specifications